CONSTITUTIONALITY ISSUES OF PARATE EXECUTION IN SHARIA ECONOMIC DISPUTES (CASE STUDY OF DECISION NUMBER 950/PDT.G/2019/PA.JP) - Muhamad Dadi Dwiono; A. Rachmad Budiono; Siti Rohmah (CV. RADJA PUBLIKA, 2025)
Parate execution is a mechanism of direct enforcement without prior judicial proceedings, as regulated under Article 6 of Law No. 4 of 1996 concerning Mortgage Rights. However, this mechanism often conflicts with Article 224 HIR/258 R.Bg, which requires execution through court execution by court fiat. This study examines the constitutionality of Article 6 in relation to Article 224 HIR/258 R.Bg, using Central Jakarta Religious Court Decision No. 950/Pdt.G/2019/PA.JP as the primary case study. It also analyses the concept of justice in Islamic law and Jeremy Bentham’s theory of legal utility. The findings reveal a normative conflict that creates legal uncertainty and undermines substantive justice, particularly in Sharia-based financing. Harmonisation between statutory law and Islamic legal principles is therefore necessary to achieve legal certainty and substantive justice.